2020
DOI: 10.1016/j.jbusres.2020.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Individual and team entrepreneurial orientation: Scale development and configurations for success

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
214
0
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(261 citation statements)
references
References 102 publications
10
214
0
12
Order By: Relevance
“…Elaborating on the links of IEO to specific contextual factors, such as cultural factors, political environment, legal frameworks, macro-economic and micro-economic environment, Kollmann et al (2007) developed a conceptual framework of IEO as behavior molded by contextual influences. Similarly Covin et al (2020) observed the influence of the context on IEO, noting that the informal sector entrepreneurship context and its dynamics may influence IEO. In line with these perspectives, IEO can be used to explain the emergence of entrepreneurial leadership in informal sector entrepreneurship.…”
Section: Individual Entrepreneurial Orientation and The Emergence Of mentioning
confidence: 73%
“…Elaborating on the links of IEO to specific contextual factors, such as cultural factors, political environment, legal frameworks, macro-economic and micro-economic environment, Kollmann et al (2007) developed a conceptual framework of IEO as behavior molded by contextual influences. Similarly Covin et al (2020) observed the influence of the context on IEO, noting that the informal sector entrepreneurship context and its dynamics may influence IEO. In line with these perspectives, IEO can be used to explain the emergence of entrepreneurial leadership in informal sector entrepreneurship.…”
Section: Individual Entrepreneurial Orientation and The Emergence Of mentioning
confidence: 73%
“…Thus, users and potential providers of coworking spaces quickly become aware of the solutions explaining why the emergence of coworking spaces as a general solution of work and social space occurs under high dynamic. Thus, the network and IT-focus of coworking spaces and their users' background triggers the fast diffusion of coworking spaces as a new solution for entrepreneurship, especially for digital business world-wide (Cesinger et al 2016;Bouncken et al 2018c;Covin et al 2020).…”
Section: Speed Out Of the Digital Work Backgroundmentioning
confidence: 99%
“…Coworking spaces will exert some regulative forces refer to rules, the monitoring of conformity to them, the definition and enactment of sanctions, rewards to influence desired behaviors. This might steer or favor certain business models or entrepreneurial ideas (Kraus et al 2019;Covin et al 2020;Bouncken 2004;Clauss et al 2020). Rules concern the admittance of what individual and corporate users and project structures among them.…”
Section: Mutability Internal Contradictions and Multiplicity Of Rulementioning
confidence: 99%
“…However, it is not only owners or management teams of organizations who can propose innovative and proactive actions, but any member of the organization (Hughes et al, 2018). Hence, the individual entrepreneurial orientation (IEO) construct has caught the attention of academics in recent years (Bolton & Lane, 2012;Covin et al, 2020;Kraus et al, 2019). In this context, Covin et al (2020) define IEO as a 'tendency held by individual employees of the organization towards innovative, proactive, and risk-taking behaviors in the workplace' (p. 2).…”
Section: Entrepreneurial Orientationmentioning
confidence: 99%